Obesity and smoking: can we catch two birds with one tax? - Davide Dragone; Francesco Manaresi; Luca Savorelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
The debate on tobacco taxes and fat taxes often treats smoking and eating as independent behaviors. However, since there exists medical and sociological evidence about the interdependence between eating and smoking choices, antismoking policies may also affect the obesity prevalence and fat taxes could influence smoking behavior. We address this issue from a theoretical standpoint and propose a dynamic rational model where eating and smoking are simultaneous choices that jointly affect body weight and addiction to smoking. Focusing on direct and cross price effects, we compare tobacco taxes and fat taxes and we show that a single policy tool can reduce both smoking and body weight. In particular, fat taxes can be more effective than tobacco taxes at simultaneously fighting obesity and smoking.
Keywords: D91; H31; I18; 330